Effect of viscosity and temperature on the microstructure of BBT thin films - Costa, Gustavo Carneiro Da [UNESP]; Simões, Alexandre Zirpoli [UNESP]; Gasparotto, Gisele [UNESP]; Zaghette, Maria Aparecida [UNESP]; Stojanovic, Biljana [UNESP]; Cilense, Mario [UNESP]; Varela, José Arana [UNESP] (ABM, ABC, ABPol, 2003)
Thin films of BBT were deposited on silicate and Pt/Ti /SiO2 (111) substrates by spin- coating from the polymeric precursor method (Pechini process). The obtained films were characterized by optical microscopy, X-ray diffraction and atomic force microscopy. The influence of viscosity on the morphology of BBT thin films as well as the influence of temperature on crystallization, morphology and properties of BBTare discussed. Surface roughness and crystallization of these films are strongly dependent on the annealing conditions.
Keywords: BBT; thermal treatment; viscosity